Administrative Services for Making Marriage Certificates at the Office of Religious Affairs, Jejawi District, Ogan Komering Ilir Regency - Arry Halbadika Fahlevi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2021)
The method used in this study is a qualitative descriptive method in which a method related to data collection, while the data used are: interviews and observations. The purpose of this study was to determine the administrative services of making Marriage Certificates at KUA Jejawi District. From the results of interviews conducted with the Head of KUA, the administration, and Administration, the results of the research conducted indicate that the role of administration in improving the service of making Marriage Certificates is still low, this is due to the employee who takes care of the administration by only one person, and the lack of execution of tasks guidance and empowerment services in planning activities in the manufacture of Marriage Certificates.